EFFECT OF PERSONAL VALUE TOWARD E-SHOPPING BEHAVIOR THROUGH ATTITUDE TOWARD E-SHOPPING ATTRIBUTES - TRIJAYANTI, VANDA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
Nowadays internet has been used for selling product or e-shopping. Intention people to shop via internet is still low. For this reason, one of the problems on online shop is how to convert visitors into buyers. One of the solution is using personal value approach . The purpose of this study is to investigate the effects of personal value in e-shopping behavior when applied with attitude toward e-shopping attributes. The sampling method that used in this study is purposive sampling with a sample of people that ever shopped via internet in â€œGraciaâ€ online shop fashion . Data analysis using Structural Equation Modelling (SEM) method with Lisrel software. The results of this study indicate that personal value has a very significantly positive effect on consumers attitude toward e-shopping attributes, which is give 0,73 (73%) value in return. Whenever consumer have a positive attitude toward e-shopping attributes, then it will give a self motivation for them to do online shopping behavio